Comparative analysis of the competitive activity of the strongest and ukrainian forces greco-roman style. - Ю. А. Радченко; Г. В. Коробейников; Л. Г. Коробейникова; В. В. Шацьких; А.В. Воронцов (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
Conduct a comparative analysis of the competitive activities of the winners and Ukrainian wrestlers, participants of the World Cup 2017. Material: The analysis of 102 competitive duels, the World Championship in 2017, studied the specifics of the application of technical and tactical actions performed by athletes. To study the characteristics of competitive activities, methods were used: analysis of video materials of competitive fights of the World Championship, statistical processing of mathematical data, pedagogical observations. Results: It is revealed that the winners of the competitions lead a massive struggle, they have the best high-speed qualities, and they quickly rebuild during the course of the fight. To effectively implement technical and tactical actions in the modern struggle, it is necessary to increase the number of preparatory actions, to conduct an active struggle for capture and a better position, to take into account the specifics of competition rules. The absence of standard provisions significantly reduced the technical arsenal of the use of precisely the methods of the Greco-Roman struggle and increased the requirements for technical and tactical and functional training. Conclusions. It was discovered that world leaders of modern Greco-Roman wrestling skillfully adapted to the requirements of the rules of the competition and successfully applied their technical arsenal, taking into account their peculiarities. Lack of standard positions during the fight requires more active struggle for capture and better position, increasing the number of preparatory technical and tactical actions, speed and powerful performance, taking into account the features of the existing rules of the competition. The training of skilled wrestlers of the Greco-Roman style in the future should take place taking into account the universalization of tactics, individuality of technology, which in turn requires an increase in the level of general and special physical preparedness. The data obtained leads to the need to adjust and improve the process of training Ukrainian wrestlers.